A novel SO2 capture, storage and utilisation to prepare BaSO3 micro-particles. (29th July 2017) - Zhang, Fei; Liu, Lihua; Zhao, Tianxiang; Guo, Bo; Sha, Feng; Qiao, Xianshu; Zhang, Jianbin
Abstract: A highly efficient SO2 capture system was developed. The system consisted of equimolar ethanediamine (EDA) and ethylene glycol (EG), and could chemically transform SO2 into a novel solid material, denoted as SO2 SM, under mild condition. This system showed a considerable SO2 storage capacity up to 0.7696 g/g (EDA + EG). Furthermore, the aqueous solution of SO2 SM was used to prepare BaSO3 micro-particles. During the reaction, EDA and EG were released from the SO2 SM and served as a directing agent and dispersant in making BaSO3 crystals that had a porous structure. Thus, the combined process enabled the comprehensive utilisation of SO2 and could convert SO2 into a value-added chemical.